Pelatihan dan Pendampingan Optimalisasi Referensi Karya Ilmiah Menggunakan Reference Manager pada Mahasiswa Prodi PGMI FTIK Iain Pekalongan - Arditya Prayogi; Rhischa Assabet Shilla (IAHN Gde Pudja Mataram, 2023)
This PKM activity aims to help students majoring in PGMI IAIN Pekalongan in strengthening the process of writing scientific papers by optimizing the use of Reference Management. This is motivated by a lack of knowledge of writing scientific articles properly and a lack of understanding in using reference management applications. Thus, the solution offered is the provision of material on strategies for writing appropriate scientific articles, and the provision of material on the use of reference management applications with VOS Viewer, Publish or Perish, and Mendeley. The methods used are in the form of lectures, discussions, online practicum, as well as assistance to partners in optimizing the use of reference management. From the results of the activity, it was found that this service activity had an impact on the academic life of PGMI students, especially on the function of determining the initial theme of scientific work and on the management of the references needed. In follow-up efforts, assistance is also provided in several ways, including textually, virtual (online), as well as offline/direct-limited so that the problems encountered can be immediately resolved.